Crohn's Disease with Oral Onset - A Case Report - M Basirat; A pakfetrat; N Kakaei; B Rohani; N bashardoust (Islamic Azad University, 2016)
Background: Crohn's disease is an inflammatory bowel disease that can affect any part of the gastrointestinal (GI) tract including the mouth. Bowel symptoms are predominant. Oral involvement may precede the GI symptoms. This case report presents a patient affected by Crohn's disease with oral onset. Case presentation: We present a 30-year-old pregnant woman complaining of chronic, multiple, yellow-white crusted ulcers predominantly involving the lips. In addition, there were small painless lesions on the palate, buccal and labial attached gingivae, alveolar mucosa and vestibule. The lesions were present since 3 months ago. The patient had not previously experienced any oral lesions or systemic diseases. The laboratory tests were normal.  Laboratory investigation showed increase in neutrophil and eosinophil count. Incisional biopsy of the buccal mucosal lesions was performed. In histopathological examination, acanthotic and parakeratotic epithelium with intraepithelial clefts was observed. Inflammatory cells such as eosinophil and polymorphonuclear (PMN) leukocytes were profoundly present in the clefts and diffusely in the epithelium. Blood vessels, collagen fibers and in-depth muscle and fat tissues were also observed. Based on these characteristics, the diagnosis of pyostomatitis vegetans was made. Considering the biopsy results and the presence of GI symptoms such as abdominal pain and diarrhea after postpartum, Crohn's disease was suspected and therefore, the patient was referred to a gastroenterologist for definitive diagnosis and treatment. The patient showed the diagnostic signs of Crohn's disease. Conclusion: This report emphasizes the important role of oral lesions as the first sign in the diagnosis of systemic diseases.